Comparison of Oral Tolerance to ApoB and HSP60 Peptides in Preventing Atherosclerosis Lesion Formation in Apob48−/Ldlr− Mice. (6th February 2013) - Mundkur, Lakshmi; Mukhopadhyay, Rupak; Deshpande, Vrushali; Samson, Sonia; Tarate, Sagar; Varma, Meenakshi; Sneha, T. S.; Lu, Xinjie; Kakkar, Vijay V.
Abstract : Antigen-specific immune modulation is emerging as an attractive therapeutic option to prevent atherosclerosis. We compared the efficacy of oral administration of peptides derived from apolipoprotein B (ApoB; 661–680) and heat shock protein 60 (HSP60; 153–163), in the prevention of atherosclerotic lesion formation hyperlipidemic low density lipoprotein receptordeficient (LDLr −/− ), apolipoprotein B-100 only (apoB 100/100 ) mice model. Oral administration of peptides induced tolerance as seen by an increase in regulatory T cells in the peripheral immune system. Tolerance to ApoB peptide reduced plaque development by 28.7% (P < 0.001 ) while HSP60 was effective in reducing lesion development by 26.8% in ApoB48/LDLr −/− mice. While tolerance to HSP60 resulted in increase in anti-inflammatory cytokines (IL10 and TGF- β ), ApoB tolerance was effective in reducing the lipid deposition in the lesion. Our results suggest that the two peptides have distinct mechanisms of controlling the development of atherosclerosis in mice.